Pengaruh Struktur Kepemilikan dan Faktor Keuangan terhadap Kebijakan Dividen - Benu, Yohanes Rudolf (E-Jurnal Akuntansi, 2020)
The ownership structure and financial factors are considered influential to the dividend policy of a company. Thus the aim of this study is to examine the effects of institutional ownership, managerial ownership, liquidity, leverage, and profitability on dividend policy. This study uses quantitative approach and analyzes samples taken from the financial statements of 161 different manufacturing companies listed in the Indonesian Stock Exchange between 2015-2017. These samples are then selected using purposive random sampling in which only 49 samples fit the criteria. The data analysis technique used is the multiple linear regression analysis technique. This study concludes that institutional ownership, managerial ownership, liquidity, and profitability have positive and significant effects on dividend policy. However, leverage has a insignificant effect on dividend policy. Keywords: Dividend Policy; Institutional Ownership, Managerial Ownership; Liquidity; Leverage; Profitability.